Penggunan Safety Stock Order Untuk Mengatasi Delay Waktu Pada Proses Produksi Paracetamol Infus disalah Satu PT. Farmasi Di Sukabumi - Agus, Agus suparna; Mukhlis Ali (Universitas Nusa Putra, 2023)
In a company, of course there are lots of problems that often occur even though the system is running properly. Such as delays in goods, machine errors, transportation equipment, and others. With supply chain management, it is one of the most important factors that will be used to support and regulate operational activities in it. This research relates to the availability of raw material stocks which aims to avoid stockouts and meet demand levels. If done right, this system will increase the efficiency of supply chain management and reduce inventory costs. The main purpose of establishing the term safety stock related to inventory is to get a profit that is more in line with expectations in the company concerned. Profit will indeed be the most important factor that must be considered when building a company. The method applied is safety stock, which is an inventory prepared by a company to prevent inventory shortages when market demand is unstable, collecting data before delays occur, and calculating the required safety stock.